Design of Temporary Shelter Layout with Reuse, Reduce, Recycle Method (TPS-3R) and SNI 19-2454-2002 at Widyatama University - Muchammad Fauzi; Verani Hartati; Setijadi; Moch Anbiya Rachmatullah (Jurnal Rekayasa Sistem & Industri, 2024)
Based on the performance achievements of the Ministry of Environment and Forestry, in 2023 unmanagedwaste amounted to 5,899,371.35 tons/year. The data shows that there is still a waste management process atthe upstream level that is not optimal. The downstream of waste, namely landfills, is an obstacle due toexcess capacity. It was recorded that 38 landfills burned in 2023 in a number of regions in Indonesia. Oneof the landfills that caught fire was the Sarimukti landfill located in Bandung. Before the waste is finallydumped in the landfill, the waste will transit in the TPS. The purpose of this study was to design a layout atthe Widyatama University TPS using the TPS-3R method and SNI 19-2454-2002. Observations andobservations were made in June and July 2023 at Widyatama University TPS to see the condition of wastegeneration and TPS buildings, while the observations made were measurements of the TPS area andidentification of the current layout conditions. The proposed layout design for Widyatama University TPSis divided into 5 places based on the largest waste category, namely: leaf organic waste with a size of 1 x 1.5x 1 m; food waste organic waste with a size of 1 x 1.5 x 1 m; plastic inorganic waste 1.5 x 1.5 x 1 m;cardboard / paper inorganic waste with a size of 1.3 x 1.5 x 1 m; and styrofoam inorganic waste with a sizeof 0.7 x 1.5 x 1 m. At the TPS, a mixed waste outpouring area is also made as a waste bin before sorting,then an organic waste processing area is made which contains an organic waste chopping machine, and acontainer is prepared as a storage area for residual waste.